2020
DOI: 10.3390/foods9111671
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Greek Oregano (O. vulgare L. subsp. hirtum (Link) Ietswaart) and Common Oregano (O. vulgare L. subsp. vulgare) Cultivated in the Temperate Climate of Central Europe

Abstract: The purpose of the study was to determine the differences between two subspecies: O. vulgare L. subsp. hirtum (Link) Ietswaart (Greek oregano) and O. vulgare L. subsp. vulgare (common oregano) growing in cultivation conditions within temperate climate of Central Europe. The characteristic of the subspecies was undertaken in terms of selected morphological parameters and the quality of the raw material. The herb of both subspecies was evaluated on the content and composition of essential oil by hydrodistillatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 59 publications
0
45
0
Order By: Relevance
“…Farnesene belongs to the sesquiterpenoid family that has a similar action mechanism with monoterpenes. They are the main component in plants essential oils and have a broad spectrum in antimicrobial activity ( 62 ). It was reported that farnesene play a significant role during oxidative injury of eukaryotic cells ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…Farnesene belongs to the sesquiterpenoid family that has a similar action mechanism with monoterpenes. They are the main component in plants essential oils and have a broad spectrum in antimicrobial activity ( 62 ). It was reported that farnesene play a significant role during oxidative injury of eukaryotic cells ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the most common secondary metabolites ranged between carvacrol and thymol [5], or terpinen-4-ol, thymol and cis-sabinene hydrate [4,33], the last of these was not identified in our sample, and it should be recalled that the chemical composition of a plant species may vary with the geographical origin and the harvest period [5], since environmental factors may influence types and contents of bioactive substances [34,35]. In addition, according to the widely accepted taxonomy, six subspecies of O. vulgare L. have been recognized [36], and the botanical subspecies which we evaluated (O. vulgare L. subsp. hirtum) does not have high levels of this component; indeed, our findings are in accordance with the typical composition of this subspecies (high levels of carvacrol and p-cymene) [37][38][39].…”
Section: Resultsmentioning
confidence: 94%
“…Therefore, in the investigated plants, a lower quantity of phenolic compounds was found in our study than in O. vulgare from countries with warmer climates [ 3 , 19 , 34 , 35 ]. This may also be due to the chemotypic features of the studied samples of O. vulgare , since the literature contains numerous data on the existence of several chemotypes differing in composition and amount of phenolic and terpene compounds in the essential oils of oregano [ 36 , 37 , 38 ]. In European populations of oregano, the chemotype of linalool predominates; there is also a cymyl chemotype or sabinyl chemotype that co-occurs with a sesquiterpene-type poor in monoterpenes [ 39 ].…”
Section: Resultsmentioning
confidence: 99%